2001
DOI: 10.1078/0944-5013-00111
|View full text |Cite
|
Sign up to set email alerts
|

Perchlorate and nitrate reductase activity in the perchlorate-respiring bacterium perclace

Abstract: The perchlorate (ClO4(-))-respiring organism, strain perclace, can grow using nitrate (NO3(-)) as a terminal electron acceptor. In resting cell suspensions, NO(-) grown cells reduced ClO4(-), and ClO4(-) grown cells reduced NO3(-). Activity assays showed that nitrate reductase (NR) activity was 1.31 micromol min(-1) (mg protein)-1 in (ClO4)- grown cells, and perchlorate reductase (PR) activity was 4.24 micromol min(-1) (mg protein)(-1) in NO3(-) grown cells. PR activity was detected within the periplasmic spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 14 publications
2
40
0
Order By: Relevance
“…It has been found that some PRB, for example Dechloromonas agitata CKB , can respire using perchlorate but not nitrate. In a PRB capable of denitrification (strain perclace), it was found that nitrate and perchlorate reductases were located in different cell fractions (membrane and periplasmic fractions, respectively), indicating that these two enzymes were separate (Giblin and Frankenberger, 2001). Further evidence of completely separate denitrifying and perchlorate pathways was provided by Xu et al (2002).…”
Section: Clomentioning
confidence: 78%
“…It has been found that some PRB, for example Dechloromonas agitata CKB , can respire using perchlorate but not nitrate. In a PRB capable of denitrification (strain perclace), it was found that nitrate and perchlorate reductases were located in different cell fractions (membrane and periplasmic fractions, respectively), indicating that these two enzymes were separate (Giblin and Frankenberger, 2001). Further evidence of completely separate denitrifying and perchlorate pathways was provided by Xu et al (2002).…”
Section: Clomentioning
confidence: 78%
“…The main source of chlorate contamination is chlorine dioxide (ClO 2 ) bleaching in the pulp and paper industry (8), and the most efficient remediation techniques for both chlorate and perchlorate are based on degradation performed by microorganisms (13,33,43). More than 40 bacterial strains that are able to grow by dissimilatory perchlorate or chlorate reduction have been isolated (2,6,10,13,15,18,21,22,24,36,37,39,40). They are phylogenetically diverse, with members in the Alpha-, Beta-, Gamma-, and Epsilonproteobacteria (13,15).…”
mentioning
confidence: 99%
“…These results showed that the optimal mass concentration ratio of acetate to perchlorate was approximately 5 (molar ratio of 8.5). This molar ratio of PMJ was much larger than previously-isolated PCRBs (molar ratio of 1∼3.2) (Giblin and Frankenberger 2001;Logan et al 2001;Nerenberg et al 2006;Rikken et al 1996;Waller et al 2004;Xu et al 2004), but these previously reported acetate concentrations were merely culture conditions. Besides, the results were similar to those of recent reports (Xu et al 2015;Zhu et al 2016) in that Azospira sp.…”
Section: Concentration Effects Of Perchlorate and Acetatementioning
confidence: 84%
“…KJ (Bardiya and Bae 2011;Xu et al 2015) in which nitrate reduction was inhibited by the perchlorate. For another case, Giblin and Frankenberger (2001) (Fig. 6).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation